2005
DOI: 10.1161/01.str.0000166195.63276.7c
|View full text |Cite
|
Sign up to set email alerts
|

Use of Quantitative Magnetic Resonance Angiography to Stratify Stroke Risk in Symptomatic Vertebrobasilar Disease

Abstract: Background and Purpose-Symptomatic vertebrobasilar disease (VBD) carries a high risk of recurrent stroke. We sought to determine whether a management algorithm consisting of quantitative hemodynamic assessment could stratify stroke risk and guide the need for intervention. Methods-All patients with symptomatic VBD at our institution are evaluated by a standard protocol including quantitative magnetic resonance angiography (QMRA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
107
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 140 publications
(109 citation statements)
references
References 28 publications
0
107
1
1
Order By: Relevance
“…[6][7][8][13][14][15][16][17] Before any treatment, mean WSS among 48 feeder arteries in our study was significantly higher compared with the mean WSS in the contralateral vessel (29.7±12.0 dynes/cm 2 versus 23.3±11.0 dynes/ cm 2 ; P=0.007). This result reveals that cerebral AVMs are a high WSS pathology, which disputes Rossitti and Svendsen's hypothesis that WSS in arteries supplying AVMs is the same as in arteries within normal brain parenchyma.…”
Section: Discussioncontrasting
confidence: 49%
“…[6][7][8][13][14][15][16][17] Before any treatment, mean WSS among 48 feeder arteries in our study was significantly higher compared with the mean WSS in the contralateral vessel (29.7±12.0 dynes/cm 2 versus 23.3±11.0 dynes/ cm 2 ; P=0.007). This result reveals that cerebral AVMs are a high WSS pathology, which disputes Rossitti and Svendsen's hypothesis that WSS in arteries supplying AVMs is the same as in arteries within normal brain parenchyma.…”
Section: Discussioncontrasting
confidence: 49%
“…5,[8][9][10][11][12] We found that mean flow dropped on average by 29% after a single embolization session and by 75% at the end of all embolization sessions. Interestingly, the drop in flow per session did not correspond to occlusion of an intranidal fistula or the number of pedicles embolized in that single session, suggesting redistribution of flow through remaining compartments of the nidus in the setting of partial embolization, as posited by Kaspera et al 14 On the other hand, mean flow after completion of all embolization sessions correlated with both the total number of pedicles embolized and embolization of a high-flow fistula, with total pedicles embolized remaining predictive in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 60%
“…This QMRA technique has been validated using in vitro and in vivo models and has demonstrated utility in the hemodynamic evaluation of cerebrovascular pathologies and interventions, including extracranial carotid artery stenosis, intracranial angioplasty/stenting, carotid endarterectomy, and extracranial-intracranial bypass. [8][9][10][11][12] Total AVM blood flow was derived based on the aggregate flow within the primary arterial feeders relative to flow in their contralateral counterparts, according to the following equation: …”
Section: Blood Flow Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Planning for pharmacological, surgical or endovascular treatment of these abnormalities of blood vessels could all benefit from insights derived from realistic models of the circulatory dynamics in the diseased arterial network. Preliminary work on the use of quantitative magnetic resonance angiography (MRA) to predict stroke appears promising (Amin-Hanjani et al 2005).…”
Section: Introductionmentioning
confidence: 99%